The Islamic Perspective of Gold-Based Investment: The Case of Indonesia - Risman, Asep; Markonah, Markonah; Mubarok, Jaih; Saputra, Budi Lestijawan Eka (Faculty of Islamic Business and Management, 2024)
Currently, there are many gold-based investment products, and investors are interested because some of them use sharia labels. Therefore, this study aims to identify and investigate gold-based investments from an Islamic perspective. It is hoped that this research can contribute new findings and enrich existing literature regarding gold investment in Indonesia, providing benefits for Muslim investors and the Muslim community in general. This study used qualitative research methods. Semi-structured interviews were conducted with parties who offer gold-based investment products on a large scale. Additional data sources include documents and manuscripts from the National Sharia Council (DSN-MUI) as well as author analysis. These findings show that not all gold-based investments in Indonesia comply with sharia principles. Only gold murabahah conducted by Islamic banking institutions meets sharia compliance.